Multiple uses of tropical forage legumes for sustainable farming in the moist savannas of Africa - Muhr, L.; Tarawali, Shirley A.; Peters, Michael; Merkel, U.; Schultze-Kraft, Rainer; Berner, D. (International Grassland Society, 1997)
Ensuring that farming in the moist savannas of Africa is maintained, despite increasing population pressure and agricultural demands, necessitates the sustainable integration of crop and livestock enterprises; a role that forage legumes can fulfill. The potential of eleven herbaceous and two shrubby species of forage legumes in an improved fallow or ley-farming system to provide dry season fodder and beneficial effects to a subsequent cereal crop were investigated. Fodder dry matter yields were highest for Stylosanthes guianensis (9.9 t/ha), Centrosema pubescens, and Aeschynomene histrix. Maize yield following S. guianensis was 138 percent higher than after natural fallow. Similar increases were obtained after Calopogonium caeruleum, Arachis pintoi and Aeschynomene histrix. Sixty accessions of A. histrix were tested for their ability to stimulate suicidal germination of Striga hermonthica and thirteen accessions were found to significantly increase germination of striga seeds; this could further enhance farmer's acceptability of this species in areas where this parasitic weed is a devastating problem.